Biomimetic Nanoparticles for the Treatment of Hematologic Malignancies. Issue 4 (8th February 2021) - Powsner, Emily H.; Harris, Jenna C.; Day, Emily S.
Abstract : Hematologic malignancies are a prevalent group of cancers that originate from abnormal hematopoietic stem cells (HSCs) in the bone marrow. As these cells differentiate to produce all blood cell types, their mutation and/or abnormal differentiation results in a wide range of diseases and complications. Current treatments for hematologic maligancies include chemotherapy and HSC transplants, both of which engender detrimental side effects that the patient must endure, and the end result is still often death. Thus, there exists a dire need for alternative methods to treat hematologic malignancies. Researchers have recently begun to explore the use of biomimetic nanotherapeutic to treat these cancers and mitigate their side effects, with promising results. Biomimetic nanoparticles (NPs) imitate naturally occurring structures such as cells through various techniques to avoid immune recognition and target specific locations in the body; by exploiting cells' expression of "self‐recognition" molecules and their unique homing abilities, biomimetic NPs can deliver therapeutic cargo precisely to diseased cells while minimizing risks of toxicity. Herein, several biomimetic nanomedicines are reviewed that are investigated as treatments for hematologic malignancies and offers perspective on the future of this approach as a therapeutic strategy. Abstract : Hematologic malignancies are a collection of often deadly disorders that stem from abnormal differentiation of HSCs in the bone marrow. Biomimetic nanoparticles (NPs) allow increased circulation time, reduced toxicity, and selective targeting of therapeutics to diseased sites in the body. These biomimetic nanomedicines are promising candidates for the effective treatment of hematologic malignancies.